Performance of compacted and stabilized clay with cement, peat ash and silica sand - Mousavi S.; Wong L.S. (Jordan University of Science and Technology, 2023)
Cements; Clay; Compaction; Compression testing; Compressive strength; Peat; Sand; Scanning electron microscopy; Shear strength; Silica; Silica sand; Soil cement; Soils; Strength of materials; CBr; Direct shear; Experimental investigations; Peat ash; Standard Proctor compaction; Unconfined compression; Unconfined compression tests; Unconfined compressive strength; Stabilization